Volatile Constituents of the Aerial Parts of Torilis leptophylla (L.) Reichenb., Thecocarpus meifolious Boiss., Leaves of Xanthogalum purpurascens Ave. Lall. and Flowers of Astrodaucus orieintalis (L.) Drude.: Four Umbelliferae Herbs from Iran - Taherkhani, Mahboubeh; Masoudi, Shiva; Rustaiyan, Abdolhossein (Asian Journal of Chemistry, 2017)
The authors retract the above article for violations of the ethical guidelines to publication. This article was published without the knowledge or consent of the author/s. As a result, the authors retract this manuscript.